Photochemistry Meets Porous Organic Cages - Hsin-Hua Huang; Tomáš Šolomek (CHIMIA, 2021)
Chemistry of porous organic cages has developed in the past decade as an alternative to the wellknown nanoporous materials based on extended networks, such as metal organic frameworks (MOFs) or covalent organic frameworks (COFs). Unlike these extended polymeric materials, the molecular nature of organic cages offers important advantages, such as solubility of the material in common organic solvents. However, a simultaneous combination of porosity and additional optoelectronic properties, common in MOFs and COFs, is still quite rare. Therefore, porous organic cages are relatively underdeveloped when compared to MOFs and COFs. Here, we highlight the rich possibilities the porous organic cages offer and discuss the recent development where interesting photophysical properties augment the porosity, including our own work.